Drinking Wells and River Water Quality Assessment in Oproama Community, Rivers State, Nigeria - , Asiton-a Asifamabia Dick; , Susan Chioma Okparanta (Archives of Current Research International, 2023)
Aims: The hand-dug wells and river water in Oproama Community, Rivers State, Nigeria was assessed for its quality. Study Design: The study involved ten (10) sampling stations consisting of seven (7) hand-dug wells and three (3) points along the Oproama River. Place and Duration of Study: Oproama Community in Asari-toru Local Government Area of Rivers State, Nigeria between January and December, 2011 to cover both dry and wet seasons. Methodology: The parameters assessed were Vibrio (bacteria), salinity, calcium, magnesium concentrations as well as saltwater intrusion status employing standard laboratory procedures and estimation model. Results: The results reveal that Vibrio counts ranged from 2 x102 to 1.375 x104 cfu/100ml and the bacteria species identified from the water sources were Vibrio cholera and Vibrio parahaemolyticus. The study also reveals that salinity ranged from 11.97 to 13,772mg/l, calcium, 0.15 to 126.33mg/l and magnesium, 0.09 to 43.02mg/l. All parameters assessed exhibited seasonal variation during the study period; Calcium/magnesium (Ca/Mg) ratios for each well water sample ranged from 1.67 to 12.33 and indicate absence of saltwater intrusion which stands at a Ca/Mg limit of 1. Conclusion: Salinity (particularly well water samples), calcium and magnesium concentrations were within recommended limit; Vibrio counts were high and its presence in drinking water has public health risk; therefore, the use of sanitary buckets and point-of-use (households use) treatment and safe storage practices of water is strongly advocated.